Comparative SEM and LM foliar epidermal and palyno‐morphological studies of Amaranthaceae and its taxonomic implications. Issue 5 (27th February 2018) - Hussain, Amara Noor; Zafar, Muhammad; Ahmad, Mushtaq; Khan, Raees; Yaseen, Ghulam; Khan, Muhammad Saleem; Nazir, Abdul; Khan, Amir Muhammad; Shaheen, Shabnum
Abstract: Palynological features as well as comparative foliar epidermal using light and scanning electron microscope (SEM) of 17 species (10genera) of Amaranthaceae have been studied for its taxonomic significance. Different foliar and palynological micro‐morphological characters were examined to explain their value in resolving the difficulty in identification. All species were amphistomatic but stomata on abaxial surface were more abundant. Taxonomically significant epidermal character including stomata type, trichomes (unicellular, multicellular, and capitate) and epidermal cells shapes (polygonal and irregular) were also observed. Pollens of this family are Polypantoporate, pores large, spheroidal, mesoporous region is sparsely to scabrate, densely psilate, and spinulose. All these characters can be active at species level for identification purpose. This study indicates that at different taxonomic levels, LM and SEM pollen and epidermal morphology is explanatory and significant to identify species and genera. Abstract : For the first time SEM and LM foliar palyno‐morphological characters were used to identify Amaranthaceae of Pakistan. Comparative SEM and LM foliar and palyno‐morphological features were found significant for the identification of Amaranthaceae species.